War crimes of targeting civilians: examining the downing of Malaysian Airliner MH-17 - Ishan Jan, Mohammad Naqib; Haruna, Abdulrashid Lawan (2014)
The downing of Malaysian Airliner MH 17 is not the first time of shooting down a civilian airliner. There were several other cases where civilian aeroplanes carrying passengers were shot down. The case of MH 17 is the recent incident that attracts condemnation from the international community. MH 17 was shot down within the territorial air space of Ukraine, an area under the control of the separatists who are fighting against the government of Ukraine. It is alleged that the airliner was downed by the separatists who are enjoying the support of the Russian government. The same accusation is levied against the Ukrainian government. Thus the article examines the shooting down of the Malaysian airliner MH 17 and determines who is responsible for the heinous crime. It examines whether the conflict in Ukraine amounts to an armed conflict under international humanitarian law (IHL) which can be linked with the downing of MH 17. The article further examines the probable responsibility and jurisdictional problems to be faced in prosecuting the crime of shooting down MH 17 and the possible claims for compensation to the victims’ family. The article posits that the situation in Ukraine is indeed an armed conflict and the shooting down of Malaysian airliner MH 17 constitutes a war crime of targeting civilians as envisaged under the Statute of the International Criminal Court (ICC). The jurisdictional problems in prosecution of the crime may be addressed by invoking universal jurisdiction. It is recommended that an international criminal investigation should be launched on the downing of MH 17 in order to find the culprits responsible for the crime for the purpose of subsequent prosecution for war crimes.